A Randomized, Double‐Blind Trial of Abatacept (CTLA‐4Ig) for the Treatment of Takayasu Arteritis. Issue 4 (8th March 2017) - Langford, Carol A.; Cuthbertson, David; Ytterberg, Steven R.; Khalidi, Nader; Monach, Paul A.; Carette, Simon; Seo, Philip; Moreland, Larry W.; Weisman, Michael; Koening, Curry L.; Sreih, Antoine G.; Spiera, Robert; et al.
Abstract : Objective: To compare the efficacy of abatacept to that of placebo for the treatment of Takayasu arteritis (TAK). Methods: In this multicenter trial, patients with newly diagnosed or relapsing TAK were treated with abatacept 10 mg/kg intravenously on days 1, 15, and 29 and week 8, together with prednisone administered daily. At week 12, patients in remission underwent a double‐blinded randomization to continue to receive abatacept monthly or switch to placebo. Patients in both study arms received a standardized prednisone taper, reaching a dosage of 20 mg daily at week 12, with discontinuation of prednisone at week 28. All patients remained on their randomized assignment until meeting criteria for early termination or until 12 months after enrollment of the last patient. The primary end point was duration of remission (relapse‐free survival). Results: Thirty‐four eligible patients with TAK were enrolled and treated with prednisone and abatacept; of these, 26 reached the week 12 randomization and underwent a blinded randomization to receive either abatacept or placebo. The relapse‐free survival rate at 12 months was 22% for those receiving abatacept and 40% for those receiving placebo ( P  = 0.853). Treatment with abatacept in patients with TAK enrolled in this study was not associated with a longer median duration of remission (median duration 5.5 months for abatacept versus 5.7 months for placebo). There was no difference in the frequency or severity of adverse events, including infection, between the treatment arms. Conclusion: In patients with TAK, the addition of abatacept to a treatment regimen with prednisone did not reduce the risk of relapse.